Totally percutaneous endovascular repair for ruptured abdominal aortic aneurysms - Tay, Shirli; Zaghloul, Mohamed S.; Shafqat, Mehreen; Yang, Chao; Desai, Kshitij A.; De Silva, Gayan; Sanchez, Luis A.; Zayed, Mohamed A. (Frontiers in Surgery, 2022)
Purpose: The PEVAR Trial demonstrated that compared to open femoral exposure, elective percutaneous endovascular AAA repair (ePEVAR) is associated with decreased perioperative morbidity and access site complications. We hypothesized that PEVAR for ruptured AAA (rPEVAR) may also improve perioperative morbidity compared to open femoral exposure (rEVAR). There are currently no reports that evaluate the utility and outcomes of rPEVAR. Materials and Methods: From 2015 to 2021, all patients who underwent an endovascular repair of a ruptured AAA at a single institution were included in the study and grouped into rPEVAR and rEVAR. Demographics, procedural details (Successful preclose technique, conversion to femoral cutdown), postoperative variables (Blood transfusion, ICU and hospital length of stay) and short-term outcomes (30-day major adverse events (30-day MAE) and 30-day femoral access-site complications (30-day FAAC)) were collected and compared with 50 historical ePEVAR patients from the PEVAR Trial. Statistical significance was determined using Chi-square or Fisher’s exact test for categorical variables, and Mann-Whitney U-test for continuous variables. Results: 35 patients were identified (21 rPEVAR; 14 rEVAR), 86% were male with a mean age of 72 ± 9 years. All patients underwent emergent endovascular aortic repair with 100% technical success. Seventeen patients (49%) presented with evidence of hemorrhagic shock and 22 patients (63%) had blood transfusion. 30-day MAE occurred in 12 patients (34%) (7 rPEVAR; 5 rEVAR). There was no difference in demographic, perioperative outcomes and 30-day MAE rate between rPEVAR and rEVAR patients. Compared to ePEVAR patient (from PEVAR trial), rPEVAR patients had higher rate of 30-day MAE (34% vs 6%; p<.006) but no difference in 30-day FAAC (19% vs 12%; p=.54). The success rate of the preclose technique was higher in ePEVAR compared to rPEVAR (96% vs 76%; p=.02), but the rate of conversion to femoral cutdown was similar between the two groups (10% vs 4%; p=.57). Conclusion: Emergent rPEVAR appears to have similar outcomes when compared to rEVAR. Although patients undergoing rPEVAR have higher 30-day major adverse events rate compared to ePEVAR, the method of percutaneous femoral cannulation does not appear to increase the overall procedural or 30-day femoral artery access-site complications.